1988
DOI: 10.1172/jci113685
|View full text |Cite
|
Sign up to set email alerts
|

Urushiol (poison ivy)-triggered suppressor T cell clone generated from peripheral blood.

Abstract: Allergic contact dermatitis to Toxicodendron radicans (poison ivy) is mediated by the hapten urushiol. An urushiol-specific, interleukin 2 (IL-2)-dependent T cell clone (RLB9-7) was generated from the peripheral blood of a patient with a history of allergic contact dermatitis to T. radicans. This clone proliferated specifically to both leaf extract and pure urushiol. Although the clone had the phenotype CD3+CD4+CD8', proliferation to antigen was blocked by anti-CD8 and anti-HLA-A, B, C but not by anti-CD4, sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 36 publications
2
9
0
Order By: Relevance
“…Tetanus toxoid-responsive lines were uniformly CD3+ CD4+ CD8-, and urushiol-responsive lines were predominantly CD3+ CD8+ (Table I). This was compatible with our previously published reports on urushiol-specific T cell lines and clones from three individuals (29)(30)(31). Several urushiol-specific lines exhibited a significant proportion of double-positive CD4+ CD8+ cells.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Tetanus toxoid-responsive lines were uniformly CD3+ CD4+ CD8-, and urushiol-responsive lines were predominantly CD3+ CD8+ (Table I). This was compatible with our previously published reports on urushiol-specific T cell lines and clones from three individuals (29)(30)(31). Several urushiol-specific lines exhibited a significant proportion of double-positive CD4+ CD8+ cells.…”
Section: Resultssupporting
confidence: 93%
“…Several urushiol-specific lines exhibited a significant proportion of double-positive CD4+ CD8+ cells. This has been confirmed with two-color immunofluorescence and reported previously for a urushiolspecific T cell clone (29). Antigen-specific lines from a fourth individual demonstrated similar findings for both urushiol (CD3+ 98%/CD4+ 35%/CD8+ 81%) and tetanus toxoid (CD3+ 93%/CD4+ 93%/CD8+ 3%).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Recently, it has been reported that soluble exogenous antigens or haptens are able to mount an MHC class I restricted response [36,37].…”
Section: Immunological Mechanismmentioning
confidence: 99%